Blood Plasma Metabolites in Diabetes-Associated Chronic Kidney Disease: A Focus on Lipid Profiles and Cardiovascular Risk - Lecamwasam, Ashani; Mansell, Toby; Ekinci, Elif I.; Saffery, Richard; Dwyer, Karen M. (Frontiers in Nutrition, 2022)
Background: We investigated a cross-sectional metabolomic analysis of plasma and urine of patients with early and late stage diabetes associated CKD, inclusive of stages 1-5 CKD, to identify potential metabolomic profiles between the two groups. Methods: This cross-sectional study recruited 119 adults. Metabolomic biomarkers were quantified in 119 non-fasted plasma and 57 urine samples using a high-throughput proton Nuclear Magnetic Resonance platform. Analyses were conducted using R with the ggforestplot package. Linear regression models were minimally adjusted for age, sex, and body mass index and p-values were adjusted for multiple comparisons using the Benjamini-Hockberg method with a false discovery rate of 0.05. Results: Apolipoprotein A1 concentration (ApoA1) was reduced (adj. p = 0.04) and apolipoprotein B/apolipoprotein A1 ratio (ApoB/ApoA1) was increased (adj. p = 0.04) in late CKD compared with early CKD. Low-density lipoprotein triglyceride (LDL-TG) had an increased concentration (adj. p = 0.01), while concentrations of high-density lipoprotein cholesterol (HDL-C) were reduced (adj. p = 0.04) in late CKD compared to early stages of disease. Conclusions: Our results highlight the presence of abnormal lipid metabolism namely significant reduction in the protective ApoA1 and significant increase in atherogenic ApoB/ApoA1 ratio. The study also demonstrates significantly elevated levels of triglyceride-rich lipoproteins such as LDL-TG. We illustrate the significant reduction in protective HDL-C in individuals with diabetic CKD. It explores a detailed plasma lipid profile that significantly differentiates between the late and early CKD groups as well as each CKD stage. The study of complex metabolite profiles may provide additional data required to enable more specific cardiovascular risk stratification.